Pengolahan Air Bersih Berbasis Kebutuhan Rumah Tangga dalam Upaya Meningkatkan Kesehatan Masyarakat di Desa Kandat Kabupaten Kediri - Ira Arundina; Theresia Indah Budhy S; Roni Handayani; Septyana Eka Rahmawati (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this community service activity is to increase awareness of Kandat Village residents through counseling about clean water treatment for household needs. This service method used a hybrid method, namely offline and online. The results of the service show that the community is aware of the need for clean water for health and daily needs. Utilization of infrastructure to facilitate clean water treatment is indicated by the construction of reservoirs. The achievement of fulfilling clean water is expected to have a positive impact, especially preventing the spread of the Covid-19 pandemic by using clean water to implement health protocols.